An African religions perspective - Wiredu, Kwasi (The Oxford handbook of religious diversity, 2011)
A very fundamental fact about African religions is that they are not institutional religions. They do not have an organization that one becomes a member of upon converting or being converted to the religion. Such an organization has a hierarchy of officials in charge of the propagation of a certain metaphysic and the promotion of virtue. One has to accept certain doctrines before qualifying to be a member of such a religion. If the religion is a God-oriented one, then a most important duty of the officialdom will be to arrange regular sessions of God worship. A considerable amount of infrastructure, such as chapel buildings, needs to be taken care of. In sophisticated instances, the maintenance of the officers alone calls for the command of good economic resources. None of these things is pertinent to traditional African religions. In the this discussion, I will first, as an Akan, frequently call upon my direct knowledge of Akan traditional religion to illustrate generalities. Second, I will offer a basic description of African traditional religion. I will then reflect on specific issues of religious diversity with respect to this traditional religion.
paid
Keywords: Africa – Religion; Akan (African people); Christianity and African religions; Evil; God (African religion); God (Philosophy); Pluralism; Religious